Development of Real-Time Dissolved Oxygen Optimizer for Caged Fish Farm - Mohd Sani Said; Muhammad Sufyan Safwan Mohamad Basir; Azhar Abdullah (International ABEC, 2021)
This paper presents the development of real-time dissolved oxygen (DO) optimiser for caged fish farm. The prototype is for maintaining the DO level especially for sea basses, red snappers and groupers. An EZO-DO sensor senses the DO level, which then is sent to an Arduino microcontroller to process the data gathered. The prototype works by triggering the DO water pump if the DO level is less than 3 mg/L, and if the DO level is less than 4.5 mg/L, the paddle wheels will spin. The proposed DO optimiser is powered by a solar panel, hence it is suitable to be implemented in remote areas that are far from lagoon. The proposed DO optimiser is expected to maintain the DO level within 3 – 7 mg/L. Future work will focus on the system performance.